2016
DOI: 10.1038/nn.4405
|View full text |Cite
|
Sign up to set email alerts
|

Unstable neurons underlie a stable learned behavior

Abstract: Motor skills can be maintained for decades, but the biological basis of this memory persistence remains largely unknown. The zebra finch, for example, sings a highly stereotyped song that is stable for years, but it is not known whether the precise neural patterns underlying song are stable or shift from day to day. Here, we demonstrate that the population of projection neurons coding for song in the pre-motor nucleus HVC change from day to day. The most dramatic shifts occur over intervals of sleep. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 52 publications
8
113
2
Order By: Relevance
“…Interestingly, the activity of inhibitory neurons was significantly less variable [37]. Recent Ca 2+ imaging data obtained with miniature wide-field microscopes provide further support for a stable population motor code with unstable single-cell participation [55]. In HVC, a pre-motor area that drives stable learned song in zebra finches, the firing patterns of individual neurons were highly variable whereas average population activity was stable.…”
Section: Stability Versus Variability In Motor Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the activity of inhibitory neurons was significantly less variable [37]. Recent Ca 2+ imaging data obtained with miniature wide-field microscopes provide further support for a stable population motor code with unstable single-cell participation [55]. In HVC, a pre-motor area that drives stable learned song in zebra finches, the firing patterns of individual neurons were highly variable whereas average population activity was stable.…”
Section: Stability Versus Variability In Motor Cortexmentioning
confidence: 99%
“…All these factors are likely to directly affect the assessment of neuronal variability. Furthermore, longitudinal recordings of cellular activity have been performed using a plethora of different experimental paradigms in multiple preparations—from in vitro recordings in dissociated cultures [58,59] to in vivo recordings in primary and higher sensory areas [14,15,18,19,29,35,36,38,39,4144,46,47,49,60], motor areas [22,27,37,48,55,6165], striatum [22] and hippocampus [28,40,45,52,6669]. Comparing the variability of neuronal feature selectively therefore is challenging—nevertheless, we would first like to provide an update on long-term neuronal variability assessments (for a previous in-depth review see [16]; for a review on short-term trial-to-trial variabiliy see [70]).…”
Section: Introductionmentioning
confidence: 99%
“…Alternately, songbirds represent a remarkable example of well-studied nonmammalian skilled motor learning, although it is not known whether principles such as basal ganglia regulation of variability (Woolley et al 2014), robust patterned activity driven by recurrent connectivity (Hamaguchi et al 2016, Long et al 2010), or modification of previously learned movement-related activity to generate new movements (Okubo et al 2015) exist in mammals. Recent work demonstrating a shifting relationship between activity in a motor region and song production in birds has provided an especially intriguing opportunity for drawing complements to the mammalian motor cortex (Liberti et al 2016). As more tools are opened up to more species, greater opportunities arise for a more comprehensive understanding of the motor cortex and mechanisms of motor control.…”
Section: Future Directionsmentioning
confidence: 99%
“…Many studies have noted stability in motor cortex activity but some have identified subtle shifts in tuning over days (Chestek et al, 2007; Ganguly and Carmena, 2009; Huber et al, 2012; Padoa-Schioppa et al, 2004; Peters et al, 2014; Rokni et al, 2007; Stevenson et al, 2011). Also, a recent study reported a mix of stable and changing features in the activity of HVC during birdsong (Liberti et al, 2016). The largest changes in neuronal activity patterns have been noted in the hippocampus.…”
Section: Introductionmentioning
confidence: 97%